Bleeding During Endoscopic Mucosal Resection - Azar, Riad R. (2011)
Endoscopic mucosal resection (EMR) has been adopted into advanced endoscopic practices in the United States as a diagnostic and therapeutic technique. The development of this technique has been a major advance in the management of early neoplastic lesions in the luminal gastrointestinal tract. It has since evolved into an effective diagnostic, staging, and treatment strategy for superficial gastrointestinal cancers. The risk of bleeding is 0.6% to 11 depending on the definition used in studies. Despite the efficacy of the currently available modalities, there is a clear need for additional techniques that may be more effective or can complement existing endoscopic treatment modalities to control bleeding during the procedure allowing for completion of the procedure and reduce rebleeding.